Pemanfaatan Area Pekarangan Sebagai Lanskap Produktif di Permukiman Perkotaan - Ahmad Sarwadi; Siti Nurul Rofiqo Irwan (Unika Soegijapranata Semarang, 2018)
Potential of yard area in urban settlements can be developed into an area that supports food security and also support the creation of a better city micro-climate. At this time, the size and shape in the yard in urban settlements is very varied, as well as variations in the types of plants. This research aims to reveal what kind and size of the yard and identifies in relation to the needs of the plants to grow. In this case, analysis of crop needs to grow is done by looking at the type of plants and the way of cultivation. This research collecting data by field observations, measurements, drawing, interviews and taking photographs. The research findings show a variety of shapes and sizes of yard area, as well as variety of plants and cultivation method. The research also found that the yard in the urban settlements is a naturally growing yard that is not developed by design. Based onfindings of research, we provide recommendation to design development of the yard.